The labour of place: Memory and extended reality (XR) in migration museums. (June 2021) - Reading, Anna; Bjork, Jim; Hanlon, Jack; Jakeman, Neil
How do we understand the relationship between memory and place in the context of Extended Reality (XR) migration museum exhibitions? The study combines a global mapping of XR within migration museums, a user analysis of Cologne's virtual migration museum, and practice-led research with the UK Migration Museum to argue that XR places in Web 2.0 constitute a multiplication of memory's significant localities. These include a migration memory's place of beginning (the location of a migrant experience), the place of production (where the memory is transformed into representation) and the place of consumption (where the mediated memory is engaged with, looked at, heard). Mnemonic labour involving digital frictions at each of these sites constitutes a form of multiple place-making with complex feelings, meanings, and (dis)connections. This points to an innovative approach to understanding and curating XR experiences with museums that recognises the significance of the labour of place.